Bishop Lucas of Túy and the Latin Chronicle Tradition in Iberia - Reilly, Bernard F. (The catholic historical review, 2007)
Lucas, bishop of Tuy, was a canon of the shrine of San Isidoro in León, protégé of Queen Berenguela, and figure at the court of her son, King Fernando III, of Leon-Castile. He was also the compiler and author of a world chronicle, Chronicon Mundi, finished about 1238. This study is particularly directed to the final nineteen chapters of his work that treat his own times, between 1188 and 1236. It is an analysis of his attitudes toward the medieval Iberian kings and kingship of that period, toward those monarchs' activities in the reconquista directed against Muslim Iberia, and toward the contemporary Church and churchmen., Lucas' Chronicon, together with the De Rebus Hispaniae of Archbishop Rodrigo Jimenez de Rada finished in 1243, and the Cronica Latina Regum Castellae, completed after 1238 probably by the chancellor of the realm and later Bishop Juan of Soria and Burgos, form part of a remarkable contemporary trilogy of Latin historical works associated with the court of Fernando III. All have also been given a modern critical edition just recently, 2003, 1987, and 1997 respectively, putting their study on a new and more reliable scholarly level. While earlier scholarship had tended to be somewhat dismissive of the Chronicon of Lucas, it here emerges as a robust contribution to the very lively Latin historical compositions of the early thirteenth century in León-Castile.